ANALYSIS FACTORS AFFECTING OPPORTUNISTIC INFECTIONS IN WOMEN HIV IN DR SOETOMO HOSPITAL - Trisnashanti, Dea Praditya; Romdhoni, Achmad Chusnu; Arfijanto, Muhammad Vitanata (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Human Immunodeficiency Virus (HIV) remains a major global health concern. In Indonesia, women account for 35.1% of HIV cases. In East Java alone, 1,062 new cases were reported between January and March 2023, with Surabaya recording the highest number at 663 cases. Opportunistic infections frequently affect HIV patients due to weakened immune systems. Tuberculosis is the most prevalent OI among HIV patients in Indonesia, accounting for 62.1% of cases, and is commonly found in women, posing a risk of vertical transmission. This study aims to analyze the factors influencing of opportunistic infections in women living with HIV. Methods: A quantitative approach with an observational analytic design and retrospective method. Used a total sampling technique involving all female HIV patients diagnosed with opportunistic infections at HIV clinic of Dr. Soetomo Hospital from January-December 2023, meet the inclusion criteria. The research was conducted from December 2023-October 2024. The dependent variable is opportunistic infections, while the independent variables are duration of HIV infection, adherence to antiretroviral therapy, CD4 cell count, and viral load. Data were analyzed using univariate and bivariate methods, with the Chi-Square test. Results: The results, duration of HIV infection was not significantly associated with opportunistic infections (p = 0.402). However, ARV adherence (p = 0.003), CD4 count (p < 0.001), and viral load (p = 0.001) were significantly associated with increased risk of opportunistic infections. Conclusion: In conclusion, ARV adherence, CD4 count, and viral load significantly influence the occurrence of opportunistic infections among HIV-positive women at Dr. Soetomo Hospital